Relation Between Cardiology Follow-Up Visits, Evidence-Based Statin Prescribing, and Statin Adherence (from the Veterans Affairs Health Care System) - Rehman, Hasan; Ahmed, Sarah T.; Akeroyd, Julia; Mahtta, Dhruv; Jia, Xiaoming; Rifai, Mahmoud Al; Nasir, Khurram; Jneid, Hani; Khalid, Mirza U.; Alam, Mahboob; Toth, Peter P.; Virani, Salim S. (The American journal of cardiology, 2019)
Statin use remains suboptimal in patients with atherosclerotic cardiovascular disease (ASCVD). We assessed whether outpatient care with a cardiology provider is associated with evidence-based statin prescription and statin adherence. We identified patients with ASCVD aged ≥18 years receiving primary care in 130 facilities and associated community-based outpatient clinics in the entire Veterans Affairs Health Care System between October 1, 2013 and September 30, 2014. Patients were divided into: (1) patients with at least 1 outpatient cardiology visit and (2) patients with no outpatient cardiology visits in the year before the index primary care visit. We assessed any- and high-intensity statin prescription adjusting for several patient- and facility-level covariates, and statin adherence using proportion of days covered (PDC). We included 1,249,061 patients with ASCVD (mean age: 71.9 years; 98.0% male). After adjusting for covariates, patients who visited a cardiology provider had greater odds of being on a statin (87.4% vs 78.4%; Odds ratio [OR] 1.25, 95% Confidence interval [CI] 1.24 to 1.26), high-intensity statin (34.5% vs 21.2%; OR: 1.21, 95% CI 1.21 to 1.22), and higher statin adherence (mean PDC 0.76 ± 0.29 vs 0.70 ± 0.34, PDC ≥0.8: 62.0% vs 57.3%; OR 1.09, 95% CI 1.09 to 1.11). A dose response relation was seen with a higher number of cardiology visits associated with a higher statin use and statin adherence. In conclusion, compared with outpatient care delivered by primary care providers alone, care delivered by a cardiology provider for patients with ASCVD is associated with a higher likelihood of guideline-based statin use and statin adherence.